Population delineation of mudskipper Boleophthalmus dussumieri (Valenciennes, 1837) from Indian waters - Das, Pritam; Bhushan, Shashi; Nayak, B. B.; P. Layana; K. V. Rajendran (Indian Journal of Fisheries, 2025)
The mudskipper Boleophthalmus dussumieri (Valenciennes, 1837) is an amphibious goby inhabiting muddy substrates, predominantly within mangrove ecosystems influenced by tidal fluctuations. In this study, a total of 292 specimens collected from Gujarat, Maharashtra and West Bengal were examined for stock differentiation using truss morphometry and parasites as biological tags. Twenty-six morphometric variables extracted from 12 anatomical landmarks were were anlysed using principal component analysis (PCA), which accounted for more than 80% of the total variation in the first two components. Linear discriminant analysis (LDA) indicated 100% correct classification, confirming the existence of three distinct stocks, with the leasr divergence observed between Maharashtra and Gujarat populations and the greatest divergence between Maharashtra and West Bengal populations. The only parasite identified, Ellipsomyxa sp., was confined to the gall bladder, but lacked the diagnostic features necessary to serve as a tag parasite for stock discrimination. Consequently, it was considered unsuitable for differentiating B. dussumieri populations. Keywords: Discriminate analysis, Factor analysis, Stock dynamics, Morphometry, Parasite